Proceedings of the 8th International Conference on Reform, Revolution and Paradigm Shifts in Mathematics Education, 25th November - 1st December 2005, Hotel Eden Garden, Johor Bahru - International Conference on Reform, Revolution and Paradigm Shifts in Mathematics Education (8th : 2005 : Johor Bahru, Johor); Universiti Teknologi Malaysia; The Mathematics Education into the 21st Century Project (Skudai : Universiti Teknologi Malaysia, 2005)
41